Economic Council of Mongolia: on the 100th Anniversary of its Establishment - Keemya V. Orlova (Монголоведение)
Introduction. 2024 marks the 100th anniversary of the founding of the Economic Council of Mongolia, the formation of which as part of the Ministry of Finance was adopted at a meeting of the People’s Government on November 18, 1924. In fact, its activities began on February 3, 1925. The main purpose of its creation was to coordinate the activities of economic bodies, develop and plan economic and financial policies and prospects for the economic development of the country. The Economic Council of Mongolia functioned until 1932, during the period of the organization’s activity four heads were replaced. In July 1932, at the 17th extraordinary meeting of the Small Khural, the Economic Council was reorganized into the State Department of Planning and State Accounting under the Council of Ministers of the country. Soviet specialists were also involved in the work at the Economic Council — E. A. Stulov (as an adviser), A. D. Simukov, etc. The purpose of the article is a preliminary overview of the activities of the Economic Council, highlighting the main forms of its work. The article uses materials from the State National Archive of Mongolia, published scientific literature. Conclusions. The main purpose of the creation of the Economic Council was to coordinate the activities of economic bodies, develop and plan economic and financial policies and prospects for the economic development of the country. Viewed from this point of view, the council, which functioned for only eight years (1924–1932), only partially fulfilled its main tasks. However, it is not yet possible to fully judge the activities of the main economic institution at that time due to the insufficiency of documents from the Mongolian and Russian archives. Soviet specialists, Advisor E. A. Stulov, employees of the Scientific Committee of Mongolia and the Economic Council, in particular its head G. Nanzad, played a major role in the work of the Economic Council.